PENGARUH KETEBALAN SPESIMEN TERHADAP NILAI KOEFISIEN PENYERAPAN SUARA MATERIAL KOMPOSIT SERBUK GERGAJI - Ariawan Bayu Wicaksono (Kohesi: Jurnal Sains dan Teknologi, 2025)
This study aims to determine the effect of specimen thickness on the sound absorption coefficient (SAC) of composite materials made from sawdust. Sawdust was made into a composite material with a volume fraction variation of 30:70 with thickness variations of 25 mm, 30 mm, and 40 mm. The samples were tested at frequencies of 200–1600 Hz using a type 4206 impedance tube with two microphones according to ASTM E1050 standards. Based on the test results, it was found that the material with a thickness of 40 mm (T40) achieved the highest SAC value with an α value of 0.18 at a frequency of 1200 Hz. It can be concluded that the sound absorption coefficient (SAC) value of the sawdust composite material increases with the thickness of the material, especially at high frequencies, because the increase in material thickness allows for more effective interaction between sound waves and the porous structure, thereby enhancing sound energy dissipation.